Microbial decomposition is highly sensitive to leaf litter emersion in a permanent temperate stream - Mora-Gómez, Juanita (2018)
Drought frequency and intensity in some temperate regions are forecasted to increase under the ongoing global change, which might expose permanent streams to intermittence and have severe repercussions on stream communities and ecosystem processes. In this study, we investigated the effect of drought duration on microbial decomposition of Populus nigra leaf litter in a temperate permanent stream (Oliveira, NW Portugal). Specifically, we measured the response of the structural (assemblage composition, bacterial and fungal biomass) and functional (leaf litter decomposition, extracellular enzyme activities (EEA), and fungal sporulation) parameters of fungal and bacterial communities on leaf litter exposed to emersion during different time periods (7, 14 and 21 d). Emersion time affected microbial assemblages and litter decomposition, but the response differed among variables. Leaf decomposition rates and the activity of β-glucosidase, cellobiohydrolase and phosphatase were gradually reduced with increasing emersion time, while β-xylosidase reduction was similar when emersion last for 7 or more days, and the phenol oxidase reduction was similar at 14 and 21 days of leaf emersion. Microbial biomass and fungal sporulation were reduced after 21 days of emersion. The structure of microbial assemblages was affected by the duration of the emersion period. The shifts in fungal assemblages were correlated with a decreased microbial capacity to degrade lignin and hemicellulose in leaf litter exposed to emersion. Additionally, some resilience was observed in leaf litter mass loss, bacterial biomass, some enzyme activities and structure of fungal assemblages. Our study shows that drought can strongly alter structural and functional aspects of microbial decomposers. Therefore, the exposure of leaf litter to increasing emersion periods in temperate streams is expected to affect decomposer communities and overall decomposition of plant material by decelerating carbon cycling in streams.